Disaggregate earning as a means to predict future cash flows in businesses - Muhammad Madyan, Annisa Harinda Permata, (Opción, 2019)
The study aims to investigate disaggregate earning as a means to predict future cash flows in businesses. The method of this research is purposive sampling with linear regression analysis techniques and multiple linear regression analysis using (α = 5%). As a result, earning has a positive and significant effect on the future operating cash flow. In conclusion, total accrual does not affect the future operating cash flow, while disaggregate earning has a significant influence and can improve the predicted results of future operating cash flows